PENINGKATAN INTERAKSI BELAJAR KALKULUS DIFERENSIAL DENGAN MENGGUNAKAN MODEL PEMBELAJARAN TIPE TEAM ASSISTED INDIVIDUALLY (TAI) PADA MAHASISWA PENDIDIKAN MATEMATIKA - Sumargiyani Sumargiyani (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2017)
This research aims to improve the learning interaction of the students of Mathematics Education Study Program of FKIP UAD Yogyakarta in Differential Calculus subject in the academic year 2015/2016 using the cooperative learning model of Team Assisted Individually (TAI) type. This research is a class action research conducted within three cycles. The research subject is the student class C of Mathematics Education Study Program of FKIP UAD in the academic year 2015/2016 taking Calculus Differential subject. The research object is the implementation of the learning using the cooperative learning model of TAI type in Calculus Differential subject conducted in the student class C of Mathematics Education Study Program of FKIP UAD in the academic year 2015/2016. The data are collected by observation, interview, and test method. The data analysis used is qualitative descriptive analysis. The research results show that the learning using the cooperative learning model of TAI type can improve the Differential Calculus learning interaction of the students of Mathematics Education Study Program of FKIP UAD in the academic year 2015/2016. It is shown by the observation results of Differential Calculus learning interaction average, those are 53,45% (fair), 71,27% (good), and 80,07% (very good) in cycle I, II, and III, respectively.